HUKUM TALAQ ISTERI KETIKA HAIDH: SATU ANALISIS HADITH DAN FIQH - Nabilah Yusof (STAI ALHIKMAH Jakarta, 2020)
Abstract This article deals with the divorce occurred during the wife’s menstrual period. It aims to examine the status of hadiths on the law of divorce during the wife’s menstrual period and also the opinion of fiqih madhab on it. The research is library research with analysis and descriptive method. Some hadiths on it are analyzed with takhrij method, either the text of hadith or the chains of transmitter (sanad). The article also analyses the opinion of fiqh scholars on the law of divorce during the wife’s menstrual period. Based on shariah, the divorce is allowed if the husband divorce the wife in non-menstrual and before having a sexual intercourse. But if the divorce occurred during the wife’s menstrual period, there are many opinions among ulama. The result of this research shows that majority ulama stated it is unlawful if if the husband divorce the wife during her menstrual period, and his divorce is unlawful. But, Ibnu Qayyim al-Jauziyyah said that the divorce is not in line with shariah and unlawful and the husband is regarded sin doer. Abstrak Artikel ini adalah berkaitan dengan Talak Isteri Ketika Haidh. Penulisan ini bertujuan untuk meneliti status hadis-hadis berkaitan hukum talak isteri ketika haidh serta pandangan mazhab fiqh mengenainya. Jenis penelitian yang digunakan adalah penelitian kepustakaan (library research) dengan menggunakan metode deskriptif-analisis. Penulis menganalisis hadis-hadis tersebut melalui kaedah takhrij (redaksi) hadis yaitu, analisis matan (teks) dan sanad hadis seterusnya meneliti pandangan para fuqaha sekitar hukum talak ketika isteri dalam keadaan haidh. Menurut hukum syarak, talak sah apabila suami menceraikan isteri pada saat isteri dalam keadaan suci yang sebelumnya tidak digauli. Namun jika talak dijatuhkan saat isteri dalam keadaan Haidh, antara jumhur dan Ibn Qayyim al-Jauziyyah serta beberapa fuqaha berbeda pandangan. Hasil penelitian menunjukkan bahwa menurut jumhur ulama, hukum suami yang mentalak isteri ketika Haidh adalah haram dan hukum talaknya adalah sah. Namun, menurut Ibnu Qayyim al-Jauziyyah, talak tersebut tidak disyariatkan dan talak yang dijatuhkan tidak sah, serta suami tetap dianggap telah berdosa.